Az önálló francia haderő létrehozása az 1940-es vereség után és a folyamat magyar közreműködői - Bene, Krisztián (Közép-Európai Közlemények, 2023)
The French army suffered a complete and devastating defeat in 1940 following the offensive by the German forces. The armistice of 22 June 1940 required the disarmament of the French army and limited its staff to 100,000, and the navy had to return to its ports. The colonies remained under the control of the new government established in Vichy and under the protection of the French colonial forces stationed there, but their fighting value was very mixed in the absence of substantial supplies from the motherland. Nevertheless, France ended the war on the side of the victors, in which the fact that some of its representatives were able to create and deploy a force that, even to a limited extent, contributed to the Allied military victory. The founder and leader of this army was General Charles de Gaulle, who, after the French defeat, set up the Free French Forces in London in the summer of 1940, which fought against the Axis powers on the side of the Allies in the following years. After the conversion of the French armed forces in North Africa, a new French force was created under his leadership which, from 1943 onwards, was able to make an effective contribution to the Allied war effort, thus making a substantial contribution to the victory of the war. In the ranks of this armed force, we also find Hungarians, whose contribution is worth mentioning, as their identity and activities have so far been unknown in both concerned countries.